Absence of Transplacental Passage of Pentosan Polysulfate During Mid Trimester of Pregnancy - Forestier, F; Fischer, A M; Daffos, F; Beguin, S; Diner, H (Thrombosis and Haemostasis, 1986)
Eight women who were going to have an abortion between the 18th and 23rd week of gestation for chromosomal abnormalities or haemoglobinopathies received intravenously 50 mg of pentosan polysulfate (PSP). Maternal results of haemostasis prior and after the injection of the drug were compared. Fetal coagulation parameters were tested on samples obtained by direct puncture of the umbilical cord under ultrasound guidance, 30 min after injection. Results were compared to those of normal fetuses at the same stage of gestation, obtained in the same conditions. In mothers’ plasma, 30 min after injection, APTT was prolonged, factor Xa generation was markedly impaired, and factor V level was deeply decreased. By contrast, no modifications of these parameters were observed in fetal plasma, 30 min after the injection of PSP to their related mothers when compared to control fetuses. Thus the absence of biological modifications induced by PSP injection could demonstrate that this drug does not cross through the placenta.
Keywords: Fetal coagulation; Pentosan polysulfate; Pharmacology